The Role of Economic Education in the Family on the Consumptive Behavior of University Students - Novitasari, Anindita Trinura (PT. BATARI EDU CALYA, 2024)
Consumptive behavior is a behavior in humans where people spend their money to fulfill needs that tend to prioritize not only needs but unrestrained wants. This behavior is identical to the tendency in spending too much money with the inability to control purchase of goods and services that are not in priority. Impulsive shopping, lack of financial planning and the tendency to prioritize prestige within their social setting. These behaviors are frequently observable among teenagers or, in this case, university students. They would be avoidable, if students have self-control to follow a rational consumption pattern. Consumptive behavior among university students should be watched carefully because it would have an impact on students’ personal wellbeing, mental health and academic advancements. Overbuying on goods should be controlled through improvement of personal financial awareness, development of prudent financial management habit and learning to differentiate between needs and wants. The family setting, as an informal education to support formal education, has a role in forming students’ mindset. Habit formation, exemplar and explanation from parents are major elements in forming a child’s mindset to behave in an economically rational way. Habits are taught by parents. Financially responsible habits are formed by the parents in their children. Through exemplars, parents provide examples on how to consume through the practices of financial management. Explanations are provided by the parents on the importance of living prudently